Kehidupan penjual koran dalam patung: Kehidupan I, II, III, dan IV karya Marida Nasution 1997 (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2022)
Jakarta is the center of all activity centers in Indonesia. Both residents and migrants who are not fortunate in the employment industry work in the informal sector, such as selling newspapers, selling drinks, and on the streets. The presence of technology has changed and brought society through various stages of civilization. Its presence creates various conveniences in carrying out activities and obtaining information, which has an impact on changes in people’s lifestyles. Currently, the means of communication such as television, newspapers, and radio are gradually being abandoned by the community. Conventional media access is now internet-based. As well as print media in the form of newspapers and magazines can now be accessed through electronic media such as the internet through various types of applications. This study will discuss how urban communities perceive the existence of newspaper sellers and the factors that influence the existence of newspaper sellers to this day. The conclusion drawn from the urban community’s view of the existence of newspaper sellers, seen from this digitalization era, is that the decline in interest in newspaper readers is not only based on the development of information and communication technology but is also based on the community’s need to find information quickly and easily. The existence of some elderly people who still do not understand using information technology is also the reason newspaper sellers are still surviving in this digitalization era.
Keywords: digitization; information; newspaper seller